Analytical solution for the influence of irregular shape loads on near borehole strain observations - Yan, Wei; Li, Zirui (Frontiers in Earth Science, 2023)
Borehole strain obseratation is widely used to study slow earthquake, volcanic activity and earthquake precursors, because of high resolution and high sensitivity, borehole strain monitoring records not only tectonic signals butalso signals from environmental disturbances. Based on the analytic displacement solution caused by the punctate load model, this paper derived the calculation formulas of peripheral strain field , provided a theoretical basis for the quantitative calculation of the load influence of borehole strain observation, and presented a method for calculating the strain effect of two-dimensional and three-dimensional irregular shape loads. The results show that: (a) To solve the problem of two-dimensional irregular shape load model, we can calculate it by vector superposition after load scattering. (b) To solve the problem of three-dimensional irregular shape load model, we can use the two-dimensional irregular shape load method to calculate with assigning different weights to the scattered points after the load scattering. The convergence processes in the vector superposition process shows the correctness and feasibility of this method, and this study can provide a research basis for quantitative analysis of influence of disturbance of peripheral load in borehole strain observation.